The preliminary study on feeding behavior of male and female little egret (Egretta garzetta) in mangrove and rice field habitats based on peck frequency - Abdullah Abdullah; Intan Zahara; Gaius Wilson (Aceh Journal of Animal Science, 2016)
The objective of  the present study was to study the differences in feeding behavior from peck frequency and type of diets, between male and female little egret (Egretta garzetta) in two different habitats, mangrove and rice fields of Banda Aceh, Sumatra, Indonesia. Focal animal sampling was used to study the feeding behavior of randomly selected birds from 07.00 AM to 06.00 PM in July 2015. Statistical analysis was conducted using t-test to test for differences between male and female peck frequency and habitats. For the combined data of both males and females, the average peck frequency of little egret (E. garzetta) observed in the mangrove and rice fields was 238.8 and 226.2 respectively. Male E. garzetta peck frequency observed was 240 pecks in mangrove habitat while female peck frequency was 225 pecks in rice field habitat. The results of our study showed that there is a significant difference in the peck frequency of little egrets observed in the two habitats (mangrove and rice fields) and between male and female E. garzetta.